2020
DOI: 10.1177/0885328220963897
|View full text |Cite
|
Sign up to set email alerts
|

Composite sponges from sheep decellularized small intestinal submucosa for treatment of diabetic wounds

Abstract: Despite the fast development of technology in the world, diabetic foot wounds cause deaths and massive economical losses. Diabetes comes first among the reasons of non traumatic foot amputations. To reduce the healing time of these fast progressing wounds, effective wound dressings are in high demand. In our study, sheep small intestinal submucosa (SIS) based biocompatible sponges were prepared after SIS decellularization and their wound healing potential was investigated on full thickness skin defects in a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The double‐layer AGS template was used as a simple regenerative device and allowed surgeons to perform a minimally invasive treatment procedure and achieve adequate granulation in an average of 2 weeks. Biological templates with sponge structures can serve as scaffolds for the regeneration of volumetric dermal or lower tissue loss without the tissue depression formation at the wound site 16 . Several in vivo experiments in animals indicated that wound dressings with sponge structures effectively promote the healing of full‐thickness skin wounds 16‐21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The double‐layer AGS template was used as a simple regenerative device and allowed surgeons to perform a minimally invasive treatment procedure and achieve adequate granulation in an average of 2 weeks. Biological templates with sponge structures can serve as scaffolds for the regeneration of volumetric dermal or lower tissue loss without the tissue depression formation at the wound site 16 . Several in vivo experiments in animals indicated that wound dressings with sponge structures effectively promote the healing of full‐thickness skin wounds 16‐21 .…”
Section: Discussionmentioning
confidence: 99%
“…Biological templates with sponge structures can serve as scaffolds for the regeneration of volumetric dermal or lower tissue loss without the tissue depression formation at the wound site. 16 Several in vivo experiments in animals indicated that wound dressings with sponge structures effectively promote the healing of full‐thickness skin wounds. 16 , 17 , 18 , 19 , 20 , 21 Some studies have indicated that sponge structures can promote wound healing more effectively than gauze or traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIS is a membranous ECM scaffold derived from porcine small intestine. It has attracted considerable attention in clinical applications for tissue regeneration, mainly because of the good capabilities of activating immune mediators, inducing angiogenesis, and promoting reepithelialization [7,43,44]. These effects are likely due to the release of growth factors, such as basic fibroblastic growth factor, transforming growth factorβ (TGF-β), and vascular endothelial growth factor (VEGF) [45,46].…”
Section: Small Intestinal Submucosa (Sis)mentioning
confidence: 99%
“…So better or novel materials are needed in both the clinic and basic research, and with the rapid development of science and techniques in biomaterials science, natural materials have attracted more and more attention. Various new natural materials have been tested for their application as patches in clinics or basic researches, like the peritoneum-fascia patch (Sarac et al, 2005), small intestinal submucosal (SIS) graft (Magden et al, 2021), bovine and porcine pericardial patch (Bai et al, 2018a;Song et al, 2021), plant-derived patch (Bai et al, 2021a;Xie et al, 2021), fish swim bladder patch (Bai et al, 2021b), and biomimetic elastin fiber patch (Bai et al, 2021c). All these materials have some merits and drawbacks (Bai et al, 2021d).…”
Section: Introductionmentioning
confidence: 99%